2015
DOI: 10.1002/lary.25389
|View full text |Cite
|
Sign up to set email alerts
|

Subjective visual vertical testing in children and adolescents

Abstract: 3b Laryngoscope, 126:727-731, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Patients with bilateral vestibular loss score similarly to control groups (Tabak et al, 1997 ; Guerraz et al, 2001 ), although a closer examination of their SVV reveals greater inter-trial variability (Funabashi et al, 2012 ). Much of the research to date has focused on visual vertical perception in adults, yet Brodsky et al ( 2016 ) have recently demonstrated that the evaluation of SVV in pediatric patients is, in fact, feasible. Furthermore, the use of a smartphone application increases participant compliance without sacrificing the sensitivity of the test to peripheral vestibular loss (Brodsky et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with bilateral vestibular loss score similarly to control groups (Tabak et al, 1997 ; Guerraz et al, 2001 ), although a closer examination of their SVV reveals greater inter-trial variability (Funabashi et al, 2012 ). Much of the research to date has focused on visual vertical perception in adults, yet Brodsky et al ( 2016 ) have recently demonstrated that the evaluation of SVV in pediatric patients is, in fact, feasible. Furthermore, the use of a smartphone application increases participant compliance without sacrificing the sensitivity of the test to peripheral vestibular loss (Brodsky et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…43,46 All of these tests have been included in studies involving child participants, but not in children with CP. 43,44,[46][47][48] The perception of upright (i.e., true vertical and horizontal) is thought to be mediated by the utricle, central utricular pathways, and vestibular cortex. 49 This function is measured using the test of SVV.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent studies have determined normative values and age/gender effects of SVV for children. 47,48 Brodsky et al 48 tested 33 children aged 7 to 18 years, n ¼ 12 typically developing and n ¼ 21 with dizziness. Typically developing children (mean age ¼ 13.9, SD ¼ 2.8) had a mean SVV of 0.7 (SD ¼ 0.5) and a score of more than 2 degrees identified children with peripheral vestibular impairment (100% sensitivity and 75% specificity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations